Integrating GWAS and transcriptomics to identify candidate genes conferring heat tolerance in rice - Li, Pingping; Jiang, Jing; Zhang, Guogen; Miao, Siyu; Lu, Jingbing; Qian, Yukang; Zhao, Xiuqin; Wang, Wensheng; Qiu, Xianjin; Zhang, Fan; Xu, Jianlong (Frontiers in Plant Science, 2023)
Rice (Oryza sativa L.) production is being challenged by global warming. Identifying new loci and favorable alleles associated with heat tolerance is crucial to developing rice heat-tolerant varieties. Here, we evaluated the heat tolerance at the seedling stage using 620 diverse rice accessions. A total of six loci associated with heat tolerance were identified by a genome-wide association study (GWAS) with ~2.8 million single nucleotide polymorphisms (SNPs). Among the six detected loci, qHT7 harbored the strongest association signal and the most associated SNPs. By comparing the transcriptomes of two representative accessions with contrasting heat tolerance, LOC_Os07g48710 (OsVQ30) was selected as a promising candidate gene in qHT7 due to the significant difference in its expression level between the two accessions. Haplotype 4 (Hap4) of LOC_Os07g48710 was determined as the favorable haplotype for heat tolerance via the gene-based haplotype analysis. The heat-tolerant haplotype LOC_Os07g48710Hap4 is highly enriched in the tropical Geng/Japonica accessions, and its frequency has decreased significantly during the improvement process of rice varieties. Based on the GWAS and transcriptomics integrated results, a hypothetical model modulated by qHT7 in response to heat stress was proposed. Our results provide valuable candidate genes for improving rice heat tolerance through molecular breeding.